Sport Governance And Indonesia's Sports Performance: Analysis Of Implementation And Implications Of Financial Scandal Cases - Maidani Maidani; Triana Yuniati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Sport governance is a fundamental aspect of managing sport organizations that plays a role in ensuring transparency, accountability and effectiveness in resource management. However, in Indonesia, the implementation of sport governance still faces significant challenges, mainly related to financial scandals, weak oversight, and lack of transparency in the management of sports grants. This research aims to analyze the implementation of sport governance in Indonesia and its impact on national sport performance using qualitative methods based on documentation studies and case analysis. Data was collected from various secondary sources, including policy documents, audit reports, previous academic studies, as well as investigative media reports on financial scandals in sports organizations. The results show that weak oversight and transparency mechanisms have led to repeated cases of misuse of funds that negatively impact athlete development, sports infrastructure, and public trust in national sports institutions. Compared to countries such as the UK and Australia that have implemented independent audit systems and strict regulations in sport governance, Indonesia still faces challenges in building professional and sustainable sport governance. Therefore, reforms in sports governance are urgently needed, including strengthening regulations, implementing an independent audit system, and reducing conflicts of interest in the leadership of sports organizations, in order to improve the competitiveness and achievements of national sports at the international level